THE PRESENT SITUATION OF THE APPLIED BEHAVIORAL ANALYSIS - Sos-Peña, M. R.; Tortosa, Francisco (Anales de Psicología / Annals of Psychology)
The application of operant techniques has proliferated in recent years across diverse types of settings, populations, journals, scientific meetings and target behaviors. Certainly, the apperance of the Journal of Applied Behavior Analysis fostered this proliferation because it formalized the autonomy of a given area of research, the Applied Behavior Analysis. This article offers a short history of the Journal of Applied Behavior Analysis, this journal is studied by means of socio-historiometric techniques. The analysis has been carried out in terms of the following indexes: the most productive authors, research groups, topics and most cited authors, works and journals. Likewise the place of this journal in present day psychology is discussed. The results shows a well structures area around a set of specific issues -including psychiarty, clinical psychology and education, among others- from a particular viewpoint, which in turn is defined by its own methodology and epistemology.